THE IMPACT OF WORK ENVIRONMENT TOWARD JOB SATISFACTION AT PT. POST MAIN BRANCH OFFICE IN MANADO - Tumboimbela, Syela C.S (Universitas Sam Ratulangi, 2018)
Abstract: Job satisfaction is a worker’s sense of achievement and success on the job. The concept of ‘workplace performance’ means that the factor of workplace environment that is being provided by the employer to their employees that could support the employees performance at work. The purpose of this research is to know the impact of work environment toward job satisfaction at PT. Post Main Branch Office Manado. This research is using a Simple Linear Regression Analysis with total sample 40 respondents that were obtained from the employee at PT. Post Main Branch Office Manado. The result shows that work environment is significantly and positively impacts the job satisfaction. Which is mean that the environment of the company is really good. The employees feel comfortable and feel safety during their work at the office. The company also provide a good facilities and treatments. Also, a factor that impact the job satisfaction at the company is effective communication between each employee and between the employees and the superiors. PT Post Main Branch Office Manado need to keep their work environment and keep maintain good relationship its employees. Keywords: work environment, job satisfaction